A CLASSICAL AYURVEDA REVIEW ON HARIDRA - Swagata Chakraborty; Aparajita Das (AYUSHDHARA, 2020)
Curcuma longa Linn. is one of the important medicinal plants of the family Zingiberaceae. Being one among the constituent of Chandraprabha vati, Mahatikta ghrita, Haridra khand, Dashamulaarista etc, Haridra is very widely used in Ayurveda for the treatment of various disorders through its Rasapanchak. The name Haridra signifies its colour. In the Ayurvedic Formulary of India, Haridra is being used in various formulations. It is used as major ingredient in many formulations. It is highly valued from time immemorial because of its vast medicinal properties, traditional usage and cosmetic value. It is extensively used as Anti-inflammatory, antibacterial, antidiabetic, anthelminthic, hepatoprotective, hypolipidemic, antihistaminic, antifungal agent. Information from Ayurvedic texts shows its wide use in the diseases like Prameha, Krimi, Aruchi, Apachi, Pandu, Visa etc. The present article provides all necessary information regarding its classical references to have an overall view of Haridra in Ayurveda.